A multi-level fuzzy switching control method based on fuzzy multi-model and its application for PWR core power control. (August 2021) - Zeng, Wenjie; Jiang, Qingfeng; Liu, Yinuo; Xie, Jinsen; Yu, Tao
Abstract: As the characteristics of complex system are usually multivariable, nonlinear, and wide operating range, it is difficult to achieve ideal control of complex nonlinear systems. To solve the problem, a multi-level fuzzy switching control method based on fuzzy multi-model is designed. The PD controller, the fuzzy controller and the fuzzy-PID controller are selected as the sub-controllers, and T-S fuzzy rules are used to realize smooth switching between sub-controllers. The multi-level fuzzy switching controller is designed as the parent controller. In this paper, the local model of PWR core is established by selecting five linear models at power levels of 20% FP, 40% FP, 60% FP, 80% FP and 100% FP, and the fuzzy multi-model of PWR core is established by weighting the five local models with triangular membership function. Then, the multi-level fuzzy switching controller with the core fuzzy multi-model is used for core power control, and the power control simulation of PWR core is carried out. The results show that the multi-level fuzzy switching controller designed based on the core fuzzy multi-model is suitable for PWR core power control. Graphical abstract: In this paper, based on the references (Li and Zhao, 2013, 2014; Liao and Wang, 2018; Chen et al., 2019; Zeng et al., 2020a), the core local models are established by selecting the linear models G P1, G P2, G P3, G P4 and G P5 at the power levels of 20% Full Power (FP), 40% FP, 60% FP, 80% FP and 100% FP. As shown in Fig. 6, the fuzzy multi-model of reactor core in the whole power level range is obtained by weighting the five local models with trigonometric membership function (Chen et al., 2019; Zeng et al., 2020a). With the core fuzzy multi-model, the MLFS controller is used for core power control, as shown in Fig. 7. A global MLFS controller is designed. The PD controller, the fuzzy-PID controller and the fuzzy controller are used to realize the effective control of core power, and the T-S fuzzy controller will distribute the weights of the three controller modes according to the error and its derivative. Image 1 Highlights: A multi-level fuzzy switching controller is designed by T-S fuzzy rules. A fuzzy multi-model is used for the whole range of PWR core operating conditions. Based on the fuzzy multi model, a multi-level fuzzy switching control system for PWR core power is established.